Integrating Psychological Capital and Islamic Spiritual Values to Build Mental Resilience in Generation Z - Nur Fadilah Ramadhany; Selvia Yolanda; Muhammad Fadhil Raihan Iryandi; Dwi Ratnasari; Zainal Arifin; Ahmad Arifi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Mental health crises among Generation Z are increasing due to digital, academic, and social pressures that contribute to anxiety, depression, burnout, and low psychological resilience. Psychological Capital (PsyCap), encompassing hope, self-efficacy, resilience, and optimism, has been shown to enhance mental well-being. However, existing PsyCap studies remain largely secular and have not extensively integrated Islamic spiritual dimensions, particularly within the context of Muslim Generation Z. This indicates a conceptual gap in developing contextually relevant mental resilience models. This study aims to develop a theoretical model of Islamic Psychological Capital (IPC) by integrating the PsyCap framework with Islamic spiritual values. It employs an integrative literature review approach, analyzing classical and contemporary books, as well as reputable national and international journal articles published between 2020 and 2025, selected for their relevance to PsyCap, mental health, and Islamic spirituality. Data analysis was conducted using thematic synthesis and conceptual mapping to identify structural relationships among key concepts. The findings reveal that PsyCap components correspond conceptually with Islamic values and can be integrated into four main dimensions: hope grounded in raja’ and tawakkal, self-efficacy based on ikhtiar, resilience rooted in sabar and ridha, and optimism derived from husnuzan and syukur. This integration produces the IPC model as a novel conceptual framework explaining the strengthening of Psychological Capital through the internalization of Islamic spiritual values. Thus, this study contributes to Islamic psychology by offering a contextual framework to strengthen the mental resilience of Muslim Generation Z amid modern disruptions.